Anton Korosˇec in slovenska manjšina na Primorskem med obema vojnama - Pelikan, Egon (Studia Historica Slovenica, 2021)
In this article, the author presents the role and importance of Anton Korošec between the world wars, in maintaining the national consciousness of Slovene and Croatian minorities in Venezia Giulia. Based on the material from the archive of Engelbert Besednjak, the author presents organized action of the Secret Christian Social Organisation and the activities of the Slovene Clergy from the Primorska region between the world wars. A crucial role in the political and especially material support for the Slovene minority was played by Anton Korošec, who took care of an ongoing funding of anti-fascist and national defence initiatives of the Secret Christian Social Organisation and the Slovene Clergy from the Primorska region. He has also cooperated with Engelbert Besednjak and other representatives of Slovenes from the Primorska region.
Keywords: Anton Korošec; Besednjak, Engelbert; Engelbert Besednjak; Italija; Julijska krajina; Kingdom of Yugoslavia; Korošec, Anton; Kraljevina Jugoslavija; narodne manjšine; Primorska; Primorska region; Primorski Slovenci; Slovene minority; Venezia Giulia